Acute effects of static and dynamic stretching on jump performance after 15 min of reconditioning shooting phase in basketball players - Annino, G.; Ruscello, B.; Lebone, P.; Palazzo, F.; Lombardo, M.; Padua, E.; Verdecchia, L.; Tancredi, V.; Iellamo, F. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The aim of this study was to assess the effects of static (SS) and dynamic stretching (DS) on vertical jump performance executed before, immediately after and at the end of the shooting phase (i.e., 15 min later), as to simulate the actual conditions preceding a match, in professional basketball players.